ANALYSIS OF METHODS AND TECHNOLOGIES FOR STRENGTHENING THE SLOPES OF THE RAILWAY ROADBED (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines how, under the influence of unfavorable climatic, hydrological, man-made and other factors, destabilizing processes occur in the soils of the body of the roadbed, which cause residual deformations of the main site and slopes of the roadbed.